PERANAN APLIKASI GO FOOD TERHADAP PERKEMBANGAN BISNIS KULINER - Tumpuan, Adiguna (Jurusan Pariwisata Politeknik Negeri Kupang, 2020)
The rapid increase in the world of information and technology has become a new phenomenon in economic development. The development of information technology will spur economic development, especially in the business world. The fast growing field of the business world today is a culinary business in its quest to open a restaurant. Not all people process their own food, coupled with a very high level of community busyness and the importance of speed and time efficiency in consuming food makes the restaurant business business considered to have a huge opportunity. In the past, consumers who wanted to enjoy food products sold had to come to the restaurant to order and enjoy their food, but recently an online application has emerged that provides food delivery services from restaurants to consumers. One of these online applications is Go-Food. Go-Food Service is a food delivery service feature developed by the Go-Jek application in March 2015. This research is a research library that aims to determine the impact of the Go-Food application on the development of the restaurant's culinary business. Data is collected from several scientific journals that are relevant to this topic